Association between whole-grain consumption, tryptophan metabolism and psychological distress: a secondary analysis of a randomised controlled trial - Liikonen, Vilma; Näätänen, Mari; Kårlund, Anna; Hanhineva, Kati; Karhunen, Leila; Kolehmainen, Marjukka (Cambridge University Press, 2025)
This study aimed to investigate whether psychological distress, whole grain consumption, and tryptophan metabolism are associated in participants undergoing weight management intervention. Seventy-nine women and men (mean age 49.7 ± 9.0 years; BMI 34.2 ± 2.5 kg/m2) participated in a 7-week weight-loss period (WL), and in a 24-week weight maintenance intervention period (WM). Whole grain consumption was measured using 4-day food diaries. Psychological distress was assessed with the General Health Questionnaire-12 (GHQ), and participants were divided into three GHQ groups based on the GHQ scores before WL. Tryptophan metabolites were determined from the participants' fasting plasma using liquid chromatography-mass spectrometry. GHQ scores were not associated with the whole grain consumption. A positive association was observed between the whole grain consumption and indole propionic acid (IPA) during the WM (p = 0.033). Serotonin levels were higher after the WL in the lowest GHQ tertile (p = 0.033), while the level at the end of the WM was higher compared to other timepoints in the highest GHQ tertile (p = 0.015 and p = 0.001). This difference between groups was not statistically significant. Furthermore, levels of several tryptophan metabolites changed within the groups during the study. Tryptophan metabolism changed during the study in the whole study group, independently from the level of psychological distress. The association between whole grain consumption and IPA is possibly explained by the effects of dietary fibre on gut microbiota. This broadens the understanding of the pathways behind the health benefits associated with the intake of whole grains.